Analysis of the PM Motor with External Rotor for Direct Drive of Electric Wheelchair - Jan Kanuch; Peter Girovsky (Communications - Scientific letters of the University of Zilina, 2019)
The paper deals with analysis of properties of synchronous motor with external permanent magnets rotor. The mathematical analysis and equivalent circuit of permanent magnet synchronous motor (SMPM) is presented. In the parts of the paper the electromagnetic design, construction design and FEM Simulation of a SMPM is described and its properties are analysed. In the paper the results of simulation in Matlab/Simulink of torque, speed and current on the base mathematical model are shown.